S1 mapping of purified nascent transcripts of simian virus 40. - Lycan, D E (1984)
We purified nascent simian virus 40 late transcripts by incubating viral transcriptional complexes, isolated from infected BSC-1 cells, in a reaction mixture that contained mercurated CTP; RNA molecules that had incorporated mercurated residues in vitro were isolated by sulfhydrylcellulose affinity chromatography. The nascent RNA was hybridized to an end-labeled HindIII C probe fragment (0.646 to 0.86 map unit), and the hybrids were analyzed by S1 mapping. Most of the products of digestion corresponded to unspliced transcripts with 5' ends mapping at nucleotides 325, 260, and 195, which are positions of the 5' ends of mature, cytoplasmic late mRNA species. In addition, two minor products diagnostic of splicing at the acceptor junctions mapping at nucleotides 556 and 443 were detected. Because the abundance of these products was not diminished by repurifying the nascent RNA through a second round of sulfhydrylcellulose chromatography, these products did not originate from contaminating non-nascent RNA. Moreover, the generation of these products was not affected when a higher salt concentration and lower temperature were used for S1 digestion, conditions that should decrease artifactual cleavage by S1 in A + U-rich regions of colinear hybrids. Therefore, it is likely that some simian virus 40 RNA chains are spliced before release from the template.